A 100 000‐year record of annual and seasonal rainfall and temperature for northwestern Australia based on a pollen record obtained offshore - Sander van der Kaars; Patrick De Deckker; Franz X. Gingele (Journal of Quaternary Science, 2006)
Pollen recovered from core tops of deep‐sea cores from offshore northwestern Western Australia were used to build climatic transfer functions applied to sediment samples from major rivers bordering the ocean in the same region and a deep‐sea core offshore Northwest Cape. Results show for the last 100 000 years, with a gap in the record spanning the 64 000 to 46 000 years interval, that from about 100 000 to 82 000 yr BP, climatic conditions represented by rainfall, temperature and number of humid months, were significantly higher than today's values. For the entire record, the coldest period occurred about 43 000 to 39 000 yr BP but it was wetter than today, whereas the Last Glacial Maximum saw a significant reduction in summer rainfall, interpreted as a result of the absence of monsoonal activity in the region. The Holocene can be divided into two distinct phases: one peaking around 6000 cal. yr BP with highest rainfall and summer temperatures; the second one commencing at 5000 cal. yr BP and showing a progressive decrease in summer rainfall in contrast to an increase in winter rainfall, paralleled by a progressive decrease in temperatures. Copyright © 2006 John Wiley & Sons, Ltd.